Determinan Penerapan Standar Akuntansi Pemerintah (SAP) Berbasis Akrual dan Dampaknya terhadap Kinerja Keuangan Pemerintah Daerah pada OPD Kota Langsa - Mayang Priska Anggraini; Meutia, Tuti; Iqlima Azhar (Jurnal Penelitian Ekonomi Akuntansi, 2024)
The purpose of this study was to examine the effect of the quality of human resources and information technology on the application of accrual-based government accounting standards (SAP) and its impact on local government financial performance in the OPD of Langsa City. The sample in this study were OPDs included in the leading sector in Langsa City which were selected using the Stratified Sampling method. Based on path analysis, it shows that the Quality of Human Resources has a positive and significant effect on the Application of Accrual-Based SAP, Information Technology has a positive and significant effect on the Application of Accrual-Based SAP, the Application of Accrual-Based SAP has a positive and significant effect on Local Government Financial Performance, the Quality of Human Resources has a positive and significant effect on Local Government Financial Performance, Information Technology has no effect on Local Government Financial Performance. Based on the sobel test, it shows that Accrual-Based SAP Implementation is able to mediate the effect of HR Quality on Local Government Financial Performance while Accrual-Based SAP Implementation is not able to mediate the effect of Information Technology on Local Government Financial Performance.